Do Antiretroviral Drugs Protect From Multiple Sclerosis by Inhibiting Expression of MS-Associated Retrovirus? - Morandi, Elena; Tanasescu, Radu; Tarlinton, Rachael E.; Constantin-Teodosiu, Dumitru; Gran, Bruno (Frontiers in Immunology, 2019)
The expression of human endogenous retroviruses (HERVs) has been associated with Multiple Sclerosis (MS). The MS-related retrovirus (MSRV/HERV-W) has the potential to activate inflammatory immunity, which could promote both susceptibility and progression towards MS. A connection between HERVs and MS is also supported by the observation that people infected with the human immunodeficiency virus (HIV) may have a lower risk of developing MS than the HIV non-infected, healthy population. This may be due to suppression of HERV expression by antiretroviral therapies (ART) used to treat HIV infection. In this pilot study, we compared RNA expression of the envelope gene of MSRV/HERV-W, as well as Toll-like receptors (TLR) 2 and 4, in a small cohort of HIV+ patients with MS patients and healthy controls (HC). An increased expression of MSRV/HERV-Wenv and TLR2 RNA was detected in blood of MS patients compared with HIV patients and HC, while TLR4 was increased in both MS and HIV patients. There was, however, no difference in MSRV/HERV-Wenv, TLR2 and TLR4 expression between ART-treated and -untreated HIV patients. The viral protein Env was expressed mainly by B cells and monocytes, but not by T cells and EBV infection could induce the expression of MSRV/HERV-Wenv in Lymphoblastoid cell lines (LCLs). LCLs were therefore used as an in vitro system to test the efficacy of ART in inhibiting the expression of MSRV/HERV-Wenv. Efavirenz (a non-nucleoside reverse transcriptase inhibitor) alone or different combined drugs could reduce MSRV/HERV-Wenv expression in vitro. Further experiments are needed to clarify the potential role of ART in protection from MS.